Laparoscopic sigmoid vaginoplasty: a salvage option for genitourinary fistula after failed McIndoe's repair. Issue 6 (30th June 2020) - Dadhwal, Rohit; Nayyar, Rishi; Krishna, Asuri; Kumar, Prashant
Abstract : A 30-year-old woman presented with vesicovaginal fistula after a forceful intercourse. She was diagnosed as a case of Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome 14 years ago and had underwent McIndoe's vaginoplasty using amniotic membrane. Similarly, another 14-year-old girl presented with an iatrogenic urethral and bladder neck injury during an attempt at McIndoe's vaginoplasty 4 months ago at another centre leading to urinary fistula with absent vagina. A laparoscopic salvage was done for both the cases along with repair of genitourinary fistula using sigmoid colon. There was no further requirement of vaginal dilation. Both patients remain fully continent at 1 year follow-up. Laparoscopic sigmoid vaginoplasty is a worthy minimally invasive salvage method for the patients of MRKH who develop fistulous complication after a previous attempt at neovagina creation. The bowel wall provides a structurally strong layer to withstand the repeated sexual trauma of the vagina.